(3JGJGQ NGfjI aj GdaJGhis - (3GdCSefOj, GdYdGA, eMeO Hf YHO GdMejO Hf GdMSjf, J (B552 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; fMeO QHfG Ydi eG CSHZ YdjfG ef GdYWGA CeG HYO abO CTGQ Edj ef ETGQJg Mce GdNGf GdCYXe hGdbgQeGf GdeYXe JGJQ NGf Cf CJTeQ dLeY cJGH LGeY ddaJGhi hGdhGbYGJ MGhj ddCMcGe hGdQhGjGJ hSejJg HGdaJGhi GdJGJGQ NGfjgs
(3BNQgG (B:s
(3hjfJgj YfO GdaUd GdSGHY YTQ aj EMQGe GdeQCI hGdeeGdjc EPG MQeJ dML GdJWhY HZjQ EPf RhLgG addRhL Gf jMdgG aj bhd YdeGFfG hGdJMdjd HGQJcGH GdeMXhQ hGdeMXhQ fhYGf Mdb TYQ hJWjjH YVh Ch LeGYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 187s
(3GdCfSGH ddSeYGfj (B1 / 108s
(3cTa GdXfhf (B1 / 268s
(3TPQGJ GdPgH (B3 / 210s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs